The Correlation between Students’ Interest in Speaking Materials and Debate Speaking Competence and Achievement at Muhammadiyah University of Bengkulu - Ridha Pratiwi; Ira Maisarah; Alamsyah Harahap (Linguistic, English Education and Art (LEEA) Journal, 2022)
The objectives of this research are to investigate the correlation between students’ interest in speaking materials and debate speaking competence then investigate the correlation between students’ interest in speaking materials and speaking learning achievement and investigate the correlation between debate speaking competence and speaking learning achievement simultaneously. This research is mix method, quantitative approach by using the correlational study as its method and qualitative. The samples of this research are 21 students. The data were gathered by using a questionnaire, interview, speaking test, and documentation value and were analysed by application SPSS. The findings showed the correlation between students’ interest in speaking materials and debate speaking competence at English student Muhammadiyah University of Bengkulu was 0.587. Furthermore, the correlation between students’ interest in speaking materials and speaking learning achievement was 0,460. In conclusion, interest in speaking materials gives a positive influence between debate speaking competence and achievement. Keywords: Interest, Speaking Competence, Speaking Learning Achievement, Speaking Materials